2019
DOI: 10.1111/radm.12390
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and tacit synergies between alliance firms and radical innovation: the moderating roles of interfirm technological diversity and environmental technological dynamism

Abstract: This study draws on theories of organizational inertia and relational view to examine how the pursuit of partnership synergy influences radical innovation in different technological contexts. We differentiate between two types of synergy: explicit synergy, defined as the potential to exchange interfirm operational elements to renew processes or capabilities, and tacit synergy, conceptualized as the potential to synthesize cross‐boundary resources to develop new perspectives or thinking modes. We find that both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…Furthermore, our findings reveal that domestic market technological and market dynamism propel emerging market SMEs to engage with their IAPD portfolio (Drnevich & West, 2021). Due to the unpredictability in their domestic markets, emerging market SEMs-especially those in the Asia-Pacific region-rely on their IAPD to gain novel knowledge to help identify technology, innovation concepts, and customer information appropriate to target foreign markets (Hao et al, 2020;Huo et al, 2018;Robson et al, 2019). In sum, our findings contribute to the relational view theory by presenting the differential domestic market environment levels under which emerging market SMEs utilize their IAPD portfolios.…”
Section: Theoretical Implicationsmentioning
confidence: 83%
“…Furthermore, our findings reveal that domestic market technological and market dynamism propel emerging market SMEs to engage with their IAPD portfolio (Drnevich & West, 2021). Due to the unpredictability in their domestic markets, emerging market SEMs-especially those in the Asia-Pacific region-rely on their IAPD to gain novel knowledge to help identify technology, innovation concepts, and customer information appropriate to target foreign markets (Hao et al, 2020;Huo et al, 2018;Robson et al, 2019). In sum, our findings contribute to the relational view theory by presenting the differential domestic market environment levels under which emerging market SMEs utilize their IAPD portfolios.…”
Section: Theoretical Implicationsmentioning
confidence: 83%
“…Knowledge sharing behaviours affect radical and incremental innovation greatly. According to Hao et al (2020), radical innovation is positively affected by both explicit and tacit synergies and such influences are dependent on “inter-firm technological diversity and environmental technological dynamism in opposing ways”. The impact of ethical leadership on radical and incremental innovation with the tacit and explicit sharing of knowledge mediating roles was investigated by Lei et al (2020) and they suggested that there is a positive relationship between ethical leadership and radical and incremental innovation.…”
Section: Review Based On Antecedents Decisions and Outcomes-theories ...mentioning
confidence: 99%
“…Recent research by Hao et al (2020) has shown that a strategic alliance as a business partnership relates to different types of synergistic effects: explicit and tacit. While explicit synergy emerges when business partners share complement assets or technologies (Zaheer et al 2013), a tacit synergy can be pursued when business partners' knowledge bases spur joint learning and inspiring innovation that could not be predicted upfront (Baum et al 2010).…”
Section: Exploring the Prerequisites Of Competence-based Synergy Of Collaborative Strategiesmentioning
confidence: 99%
“…In the last, business partners' core competencies can be integrated into new products development, and thus reframing their thinking modes, adding market value (Hernandez and Shaver 2019). For instance, (Hao et al 2020) argued that when automobile manufacturers ally "to adopt each other's core parts," they pursue an explicit synergy, whereas by synthesizing automobile technologies and rechargeable batteries, the tacit synergy "can reframe their way of thinking of how an automobile can be powered" (Hao et al 2020, p. 434).…”
Section: Exploring the Prerequisites Of Competence-based Synergy Of Collaborative Strategiesmentioning
confidence: 99%